2007
DOI: 10.2307/j.ctv2k88tqq
|View full text |Cite
|
Sign up to set email alerts
|

Moche Fineline Painting From San Jose De Moro

Abstract: Cl e l l a n d , Donald . IL D on na n , C h ri s t o p h er B. III . Co t sen I ns t i tu t e o f Ar c h a eo l o gy a t UCLA . IV. T i tl e . F3430.l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 2 publications
0
1
0
6
Order By: Relevance
“…Graham (2009: 64) has suggested that the intimate relation between the body and mortuary landscape coalesces through processional movements along familiar pathways, "stressing the extent to which the dividuality [of the dead's personhood] permeates the urban fabric of the town and consequently the lives of the inhabitants." Funerary processions in San José de Moro might have operated in exactly this way, as graphically depicted in Moche art (see Figure 3.125 in McClelland et al, 2007): bodies in progressive transformation, being dramatically manipulated through a structured sequence of movement along the space. This could have impregnated landscapes with specific personhoods, identities, and meanings of memory in contexts of community integration and mourning.…”
Section: Interpreting Huaca La Capilla: Function Design and Iconograp...mentioning
confidence: 95%
“…Graham (2009: 64) has suggested that the intimate relation between the body and mortuary landscape coalesces through processional movements along familiar pathways, "stressing the extent to which the dividuality [of the dead's personhood] permeates the urban fabric of the town and consequently the lives of the inhabitants." Funerary processions in San José de Moro might have operated in exactly this way, as graphically depicted in Moche art (see Figure 3.125 in McClelland et al, 2007): bodies in progressive transformation, being dramatically manipulated through a structured sequence of movement along the space. This could have impregnated landscapes with specific personhoods, identities, and meanings of memory in contexts of community integration and mourning.…”
Section: Interpreting Huaca La Capilla: Function Design and Iconograp...mentioning
confidence: 95%
“…Es especialmente intrigante que representaciones de esta deidad moche multifacética decreciera notablemente durante el Horizonte Medio, correspondiendo con un marcado ascenso en el número de representaciones de la diosa moche (la llamada Figura C del canon iconográfico; Lyon 1978;Benson 1988;Hocquenghem y Lyon 1990;Castillo y Holmquist 2000;McClelland et al 2007). Al mismo tiempo, la proliferación de deidades femeninas en la cerámica de Línea Fina Moche Tardío coincide con el ascenso del dios de los báculos en el arte e iconografía religiosa de la sierra.…”
Section: Las Transformaciones Religiosas Durante El Horizonte Medio Y...unclassified
“…Este importante sitio atestigua el surgimiento de las figuras políticas femeninas durante este periodo (Castillo 2006, este número). En contraste, es notable que las más lujosas tumbas de elite excavadas en el valle de Jequetepeque durante el Periodo Moche Medio precedente (400-650 d.C.) alojaran exclusivamente entierros masculinos, como ha sido documentado en el gran centro ceremonial de Dos Cabezas (Donnan 2007).…”
Section: Las Transformaciones Religiosas Durante El Horizonte Medio Y...unclassified
See 2 more Smart Citations